Rates and kinematics of active shortening along the eastern Qilian Shan, China, inferred from deformed fluvial terraces. Issue 12 (17th December 2015) - Hu, Xiaofei; Pan, Baotian; Kirby, Eric; Gao, Hongshan; Hu, Zhenbo; Cao, Bo; Geng, Haopeng; Li, Qingyang; Zhang, Guoliang
Abstract: In the eastern Qilian Shan, a flight of fluvial terraces developed along the Jinta River valley are deformed across the Nanying anticline. Four individual fluvial terraces are preserved at different elevations above the river, and higher terrace treads are draped by systematically thicker aeolian loess. Optically stimulated luminescence dating of deposits at the base of the loess provides constraints on the timing of surface abandonment; terraces were abandoned at 69 ± 4 ka B.P. (T4), 57 ± 4 ka B.P. (T3), and between 34 ± 3 ka B.P. (T2), respectively. Differential GPS measurement of the terrace profile across the anticline allows reconstruction of subsurface fault geometry; we model terrace deformation above a listric thrust fault with a tip line at 2.2 ± 0.1 km depth and whose dip shallows systematically to 23 ± 3° at depth of 5.8 ± 1.1 km. Combining terrace ages with this model of fault geometry, we estimate a shortening rate of 0.8 ± 0.2 mm/a across the Nanying fold and a shortening rate of 0.1 mm/a across the mountain front fault since 70 ka B.P. This rate suggests that the frontal fault system along the eastern Qilian Shan accomplishes crustal shortening at rates of approximately 0.9 ± 0.3 mm/a during late Pleistocene time. Key Points: Fluvial terraces are deformed across the range front of the eastern Qilian Shan Terrace deformation constrains fault geometry and displacement Chronology of terrace deposits constrains slip rates of 1 mm/yr